Group Administration as a Tool for Knowledge Sharing (International Journal of Innovative Research in Engineering & Management, 2021)
This manuscript is a treatise on the study  and analysis of entrepreneurs' future. A literature review  was conducted on major current management issues, and  assumptions about future development and its impact were  developed based on these findings. Management will  evolve in the future to accommodate a new kind of global  organization that is highly adaptable to a rapidly changing  external environment. Running a virtual firm differs from  running a traditional organization, and it will depend  heavily on communication technologies in the future,  necessitating the creation of a new corporation. According  to the results, the organizational culture and attitudes of  senior management based on individual perspectives and  management styles are negatively linked to the benefits of  perceived knowledge. A review of management efforts  shows that not all of them have been successful. For future  research, we recommend gathering data from employees,  managers, or stockbrokers and comparing the results for  more accurate information. Future study may potentially  use a large number of case studies to compare their impact  on various companies and industries.
Keywords: Employees; Information; Knowledge Sharing; Management; Value Systems